PELATIHAN PEMBUATAN LULUR SERBUK LAMUN SEBAGAI INCOME GENERATING - Pharmawati, M.; Wrasiati, L.P.; Wijaya, I.M.A.S.; Yuarini, D.A.A. (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Scrub is a cosmetic that is used to clean the skin and remove dead skin cells. Traditional scrubs are made from rice flour and herbal ingredients. One of the potential herbal ingredients is Enhalus acoroides seagrass leaf powder. Seagrass are flowering plants that live in the sea. Seagrass leaf extract contains phytochemical compounds that function as antioxidants. Scrub making training activity was given to the children of the Sunya Giri Orphanage. The products can be used to support the financial independence of the orphanage. The purpose of this activity is to train the children of the Sunya Giri Orphanage to prepare scrubs containing seagrass powder. The methods used are lectures, demonstrations and practices. Powder scrub is made by mixing rice flour with seagrass powder. Cream scrub is made with an oil phase and a water phase and then seagrass powder is added. The activity was held on August 7 2022 attended by 20 participants, 1 orphanage caretaker, and 4 Udayana University students. The activity went well with indicator that the participants could prepare powder scrubs and cream scrubs containing seagrass powder. The product outputs were powder scrubs containing seagrass leaf powder packaged in plastic pouches and seagrass cream scrubs packaged in cream pots. Keywords : Antioxidants, Enhalus acoroides, cosmetics, scrubs